Synthesis of 3,3′-methylenebis(4-hydroxyquinolin-2(1H)-ones) of prospective anti-COVID-19 drugs - Aly, Ashraf A. (Mol Divers, 2020)
ABSTRACT: During formylation of 2-quinolones by DMF/Et(3)N mixture, the unexpected 3,3′-methylenebis(4-hydroxyquinolin-2(1H)-ones) were formed. The discussed mechanism was proved as due to the formation of 4-formyl-2-quinolone as intermediate. Reaction of the latter compound with the parent quinolone under the same reaction condition gave also the same product. The structure of the obtained products was elucidated via NMR, IR and mass spectra. X-ray structure analysis proved the anti-form of the obtained compounds, which were stabilized by the formation hydrogen bond. Molecular docking calculations showed that most of the synthesized compounds possessed good binding affinity to the SARS-CoV-2 main protease (M(pro)) in comparable to Darunavir. GRAPHIC ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11030-020-10140-z) contains supplementary material, which is available to authorized users.